Flame-retardant fire-resistant cable with early warning
Patent Information
- Application Number
- CN202610898161.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]在火灾事故场景中,普通电缆极易受高温明火作用快速发生热分解、熔融滴落、绝缘层炭化破损,不仅会造成火势快速蔓延,还易引发线路短路、断电失控等次生灾害,同时传统含卤阻燃电缆在燃烧过程中会释放大量有毒腐蚀性烟气,严重阻碍人员疏散与应急救援,存在极大消防安全隐患
[0017]本发明的有益效果:本申请通过采用特殊的护套料,所述的护套料以PVC树脂为基体,在乙烯-醋酸乙烯共聚物、阻燃剂、POE接枝甲基丙烯酸缩水甘油酯、甲基乙烯基硅橡胶、润滑剂、稳定剂和抗氧剂的共同作用下,得到了具有优异的阻燃耐火性能的电缆。
Smart Images

Figure FT_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable technology, and specifically to a flame-retardant and fire-resistant cable with an early warning function. Background Technology
[0002] With the rapid development of power transmission, building power distribution, rail transit, and industrial and mining power supply, the market is placing increasingly stringent requirements on the fire resistance, flame retardancy, high temperature resistance, low smoke and low toxicity, and long-term service stability of wires and cables.
[0003] In fire scenarios, ordinary cables are highly susceptible to rapid thermal decomposition, melting and dripping, and carbonization and damage to the insulation layer when exposed to high temperatures and open flames. This not only causes the fire to spread rapidly but also easily leads to secondary disasters such as short circuits and power outages. At the same time, traditional halogen-containing flame-retardant cables release a large amount of toxic and corrosive fumes during combustion, which seriously hinders personnel evacuation and emergency rescue, posing a great fire safety hazard.
[0004] Therefore, this application is submitted. Summary of the Invention
[0005] This invention provides a flame-retardant and fire-resistant cable with an early warning function. The cable described in this application has excellent flame-retardant and fire-resistant properties.
[0006] The present invention solves its technical problem by adopting the following technical solution: A flame-retardant and fire-resistant cable includes multiple conductive cores, a filling layer, a temperature-sensing optical fiber, and a sheath layer. The multiple conductive cores are arranged in a ring array inside the sheath layer. The temperature-sensing optical fiber is located between the sheath layer and the conductive cores. The filling layer fills the space between the conductive cores, the temperature-sensing optical fiber, and the sheath layer. The sheath layer comprises the following raw materials in parts by weight: 100 parts PVC resin, 20-25 parts ethylene-vinyl acetate copolymer, 12-15 parts flame retardant, 5-8 parts POE-grafted glycidyl methacrylate, 2-5 parts methyl vinyl silicone rubber, 2-3 parts lubricant, 1-3 parts stabilizer, and 0.5-2 parts antioxidant.
[0007] As an embodiment of this application, the flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:(0.75~1.5).
[0008] As an embodiment of this application, the preparation method of the modified hydrotalcite powder is as follows: (1) Add hexachlorotriphosphazene and octaaminopropyl cage-like polysilsesquioxane to the solvent and react at 70~90℃ for 2~10h. Add γ-glycidyl etheroxypropyltrimethoxysilane and react at 50~80℃ for 2~10h to obtain the modified solution. (2) Add hydrotalcite powder to the modification solution, stir at 50~80℃ for 1~10h, and dry to obtain modified hydrotalcite powder.
[0009] As an embodiment of this application, the mass ratio of hexachlorotriphosphazene, octaaminopropyl cage polysilsesquioxane, solvent, and γ-glycidyl etheroxypropyltrimethoxysilane is (12~16):(18~24):(50~200):(20~25).
[0010] As an embodiment of this application, the solvent is at least one selected from acetonitrile, methanol, ethanol, acetone, and chloroform.
[0011] As an embodiment of this application, the mass ratio of the hydrotalcite powder to the modified liquid is 1:(2~10).
[0012] As an embodiment of this application, the average particle size of the hydrotalcite powder is 0.5~5μm.
[0013] As an embodiment of this application, the preparation method of the boron-containing flame retardant is as follows: α,ω-dihydroxypolydimethylsiloxane and boric acid are mixed and reacted at 100~140℃ for 2~10h, then maleic anhydride is added and reacted at 80~95℃ for 2~10h to obtain the boron-containing flame retardant.
[0014] As an embodiment of this application, the mass ratio of α,ω-dihydroxypolydimethylsiloxane, boric acid, and maleic anhydride is 100:(5~10):(8~12).
[0015] As an embodiment of this application, the lubricant is at least one of pentaerythritol stearate, polyethylene wax, erucamide, and oleamide.
[0016] As an embodiment of this application, the stabilizer is at least one of zinc stearate and calcium stearate.
[0017] The beneficial effects of this invention are as follows: This application uses a special sheath material, which is based on PVC resin and, through the combined action of ethylene-vinyl acetate copolymer, flame retardant, POE-grafted glycidyl methacrylate, methyl vinyl silicone rubber, lubricant, stabilizer and antioxidant, a cable with excellent flame retardant and fire resistant properties is obtained. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the structure of the flame-retardant and fire-resistant cable of the present invention.
[0019] Marked in the image: 1. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] In this invention, the technical features described in an open-ended manner include both closed-ended technical solutions composed of the listed features and open-ended technical solutions that include the listed features.
[0022] In this invention, numerical ranges are involved. Unless otherwise specified, the numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe features or characteristics, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.
[0023] In this invention, there are no particular limitations on the specific dispersion and stirring methods.
[0024] Unless otherwise specified, all reagents or instruments used in this invention are commercially available conventional products. Unless otherwise specified, the raw materials used in each comparative example and the parallel experiments of each embodiment are the same commercially available products.
[0025] PVC resin: Xinjiang Zhongtai, PVCsg5.
[0026] Ethylene-vinyl acetate copolymer: Beijing Organic, EVA 14-2.
[0027] POE grafted glycidyl methacrylate: Coase, W5D.
[0028] Methyl vinyl silicone rubber: Dongjue Organosilicon, 112-5.
[0029] Erucamide: Jinhui Taiya Chemical Reagent.
[0030] Calcium stearate: Commercially available.
[0031] Antioxidant 168: Commercially available.
[0032] Hexachlorotriphosphazene: Commercially available.
[0033] Octaaminopropyl cage-like polysilsesquioxane: Xinweichuang Biotechnology.
[0034] γ-glycidoxypropyltrimethoxysilane: Commercially available.
[0035] Hydrotalcite powder: average particle size 0.7μm, Guangsheng Rubber & Plastics, FM300.
[0036] α,ω-Dihydroxypolydimethylsiloxane: Xin'an Chemical, RTV-107-2.
[0037] Boric acid: Commercially available.
[0038] Maleic anhydride: Commercially available.
[0039] Temperature-sensing fiber optic cable: Xiaodun Technology, DTS-XD1M.
[0040] This application provides a flame-retardant and fire-resistant cable, including multiple conductive cores, a filling layer 4, a temperature-sensing optical fiber 5, and a sheath layer 6. The multiple conductive cores are arranged in a ring array inside the sheath layer. The temperature-sensing optical fiber is located between the sheath layer and the conductive cores. The filling layer fills the space between the conductive cores, the temperature-sensing optical fiber, and the sheath layer. The sheath layer comprises the following raw materials in parts by weight: 100 parts PVC resin, 20-25 parts ethylene-vinyl acetate copolymer, 12-15 parts flame retardant, 5-8 parts POE-grafted glycidyl methacrylate, 2-5 parts methyl vinyl silicone rubber, 2-3 parts lubricant, 1-3 parts stabilizer, and 0.5-2 parts antioxidant.
[0041] This application utilizes a special sheath material, which is based on PVC resin and, through the combined action of ethylene-vinyl acetate copolymer, flame retardant, POE-grafted glycidyl methacrylate, methyl vinyl silicone rubber, lubricant, stabilizer, and antioxidant, produces a cable with excellent flame-retardant and fire-resistant properties.
[0042] This application incorporates a temperature-sensing optical fiber between the sheath layer and the conductive core. This optical fiber can detect temperature changes. By placing it between the sheath layer and the conductive core, the structure of the flame-retardant and fire-resistant cable is not damaged, and maintenance is convenient. Simply connect the temperature-sensing optical fiber to the temperature measuring host to achieve temperature sensing. The host continuously scans the temperature of the entire cable in real time, and can issue an early warning when the temperature is abnormal.
[0043] In some embodiments, the flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:(0.75~1.5).
[0044] The boron-containing flame retardant described in this application contains carbon, silicon, and boron elements, and has been modified with maleic anhydride. During combustion, siloxane segments can rapidly migrate and accumulate to the surface of the cable material, forming a dense silica inorganic barrier layer. When heated, boron elements are converted into a molten boron-containing glass phase, which can wet and fill the voids and microcracks inside the carbon layer, effectively blocking the channels for oxygen and heat to conduct inward.
[0045] This application first reacts hexachlorotriphosphazene with octaaminopropyl cage-like polysilsesquioxane, and then reacts with γ-glycidoxypropyltrimethoxysilane to generate a phosphorus-containing silane graft network, which significantly improves the system's compatibility. The introduction of phosphorus further enhances the flame-retardant effect. The modified hydrotalcite obtained releases a large amount of water of crystallization and inert carbon dioxide during thermal decomposition. This dilutes the oxygen and combustible gas concentrations in the cable combustion zone, achieving physical oxygen isolation and cooling. Furthermore, the layered structure forms multiple physical barriers within the matrix, slowing down longitudinal heat transfer and the rate of thermal degradation of the matrix. Simultaneously, the composite metal oxides generated by the thermal decomposition of hydrotalcite possess excellent smoke-suppressing properties, adsorbing toxic and harmful smoke particles produced during combustion, significantly reducing the amount and toxicity of smoke generated during cable combustion.
[0046] Among them, modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:(0.75~1.5) are used as flame retardants. On the one hand, the polysiloxane and maleic anhydride of the boron-containing flame retardant can further improve the dispersibility and interfacial compatibility of modified hydrotalcite in the polymer matrix of the cable, avoid the agglomeration and accumulation of inorganic powders causing a decrease in the mechanical properties and processing performance of the material, and improve the stability of cable material molding and processing. On the other hand, modified hydrotalcite can make up for the defects of insufficient carbon layer strength of organic flame retardant polysiloxane at high temperature and easy erosion and damage by high temperature airflow. The inorganic metal oxide skeleton and organic composite carbon layer interpenetrate and interlock to jointly construct a dense protective structure. Under the synergistic effect of the two, the flame retardant and fire-resistant performance of the cable is effectively improved.
[0047] In some embodiments, the modified hydrotalcite powder is prepared by: (1) Add hexachlorotriphosphazene and octaaminopropyl cage-like polysilsesquioxane to the solvent and react at 70~90℃ for 2~10h. Add γ-glycidyl etheroxypropyltrimethoxysilane and react at 50~80℃ for 2~10h to obtain the modified solution. (2) Add hydrotalcite powder to the modification solution, stir at 50~80℃ for 1~10h, and dry to obtain modified hydrotalcite powder.
[0048] In some embodiments, the mass ratio of hexachlorotriphosphazene, octaaminopropyl cage polysilsesquioxane, solvent, and γ-glycidyl etheroxypropyltrimethoxysilane is (12~16):(18~24):(50~200):(20~25).
[0049] In some embodiments, the solvent is at least one selected from acetonitrile, methanol, ethanol, acetone, and chloroform.
[0050] In some embodiments, the mass ratio of the hydrotalcite powder to the modified liquid is 1:(2~10).
[0051] In some embodiments, the average particle size of the hydrotalcite powder is 0.5~5μm.
[0052] In some embodiments, the boron-containing flame retardant is prepared by mixing α,ω-dihydroxypolydimethylsiloxane and boric acid, reacting at 100~140℃ for 2~10h, then adding maleic anhydride, and reacting at 80~95℃ for 2~10h to obtain the boron-containing flame retardant.
[0053] In some embodiments, the mass ratio of the α,ω-dihydroxypolydimethylsiloxane, boric acid, and maleic anhydride is 100:(5~10):(8~12).
[0054] In some embodiments, the lubricant is at least one of pentaerythritol stearate, polyethylene wax, erucamide, and oleamide.
[0055] In some embodiments, the stabilizer is at least one of zinc stearate and calcium stearate.
[0056] In some embodiments, the POE-grafted glycidyl methacrylate has a melt index of 8-15 g / 10 min at 190°C and 2.16 kg.
[0057] In some embodiments, the ethylene-vinyl acetate copolymer has a melt index of 1~10 g / 10 min at 190°C and 2.16 kg.
[0058] In some embodiments, the vinyl content of the methyl vinyl silicone rubber is 0.5 to 0.79 wt%.
[0059] In some embodiments, the conductive core comprises, from the inside out, a copper conductor 1, a mica tape 2, and a semi-conductive paper tape 3 (KJ-semi-conductive tape, Kejian Co., Ltd.).
[0060] In some embodiments, the mica tape is tightly wrapped around the surface of the copper conductor by mechanical wrapping.
[0061] In some embodiments, the semiconductive paper tape is tightly wrapped around the surface of the mica tape by mechanical wrapping.
[0062] In some embodiments, the filler material is magnesium oxide.
[0063] In some embodiments, the sheath layer is applied to the surface of the conductive core and the filler layer by an extrusion process.
[0064] The present application is further illustrated below with specific embodiments:
[0065] Example 1 A flame-retardant and fire-resistant cable includes multiple conductive cores, a filler layer (magnesium oxide), a temperature-sensing optical fiber, and a sheath layer. The multiple conductive cores (three in this embodiment) are arranged in a ring array inside the sheath layer. The temperature-sensing optical fiber is located between the sheath layer and the conductive cores. The filler layer fills the space between the conductive cores, the temperature-sensing optical fiber, and the sheath layer. Each conductive core, from the inside out, comprises a copper conductor, a mica tape, and a semi-conductive paper tape (KJ-semi-conductive tape, Kejian Co., Ltd.). The mica tape is tightly wrapped around the surface of the copper conductor by mechanical wrapping, and the semi-conductive paper tape is tightly wrapped around the surface of the mica tape by mechanical wrapping. The sheath layer is wrapped around the surfaces of the conductive cores and the filler layer by an extrusion process. The temperature-sensing optical fiber is laid linearly along the axial direction of the flame-retardant and fire-resistant cable.
[0066] The sheath layer comprises the following raw materials in parts by weight: 100 parts PVC resin, 22 parts ethylene-vinyl acetate copolymer, 14 parts flame retardant, 6 parts POE-grafted glycidyl methacrylate, 4 parts methyl vinyl silicone rubber, 2.5 parts erucamide, 1.5 parts calcium stearate, and 1.2 parts antioxidant 168. The raw materials are mixed evenly according to the specified ratio, melt-extruded, and the sheath layer material is obtained. The sheath layer material is placed in an extruder and plasticized and extruded by a twin-screw extruder to coat the conductive core and filler layer surface. The barrel temperature of the twin-screw extruder is set as follows: Zone 1 175℃, Zone 2 180℃, Zone 3 190℃, Zone 4 175℃, and the die head temperature is 190℃. After cooling and forming, the material is wound up and dried at 60℃ for 2 hours.
[0067] The flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:1.
[0068] The modified hydrotalcite powder is prepared by: (1) Hexachlorotriphosphazene and octaaminopropyl cage-like polysilsesquioxane were added to acetonitrile and reacted at 85°C and 100 rpm for 7 h. Then γ-glycidoxypropyltrimethoxysilane was added and reacted at 75°C and 100 rpm for 6 h to obtain the modified solution. The mass ratio of hexachlorotriphosphazene, octaaminopropyl cage-like polysilsesquioxane, acetonitrile and γ-glycidoxypropyltrimethoxysilane was 15:22:100:24.
[0069] (2) Add hydrotalcite powder to the modification solution, stir at 100 rpm for 4 hours at 72°C, and dry to obtain modified hydrotalcite powder. The mass ratio of hydrotalcite powder to modification solution is 1:5.
[0070] The boron-containing flame retardant is prepared by mixing α,ω-dihydroxypolydimethylsiloxane and boric acid, stirring at 100 rpm for 6 hours at 118°C, then adding maleic anhydride, and stirring at 100 rpm for 5 hours at 90°C to obtain the boron-containing flame retardant. The mass ratio of α,ω-dihydroxypolydimethylsiloxane, boric acid, and maleic anhydride is 100:6.5:10.
[0071] Example 2 The difference between Example 2 and Example 1 is that the composition of the sheath layer is different, but everything else is the same.
[0072] The sheath layer comprises the following raw materials in parts by weight: 100 parts PVC resin, 20 parts ethylene-vinyl acetate copolymer, 15 parts flame retardant, 8 parts POE-grafted glycidyl methacrylate, 2 parts methyl vinyl silicone rubber, 2 parts erucamide, 3 parts calcium stearate, and 2 parts antioxidant 168.
[0073] The flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:1.5.
[0074] The modified hydrotalcite powder is prepared by: (1) Hexachlorotriphosphazene and octaaminopropyl cage-like polysilsesquioxane were added to acetonitrile and reacted at 85°C and 100 rpm for 7 h. Then γ-glycidoxypropyltrimethoxysilane was added and reacted at 75°C and 100 rpm for 6 h to obtain the modified solution. The mass ratio of hexachlorotriphosphazene, octaaminopropyl cage-like polysilsesquioxane, acetonitrile and γ-glycidoxypropyltrimethoxysilane was 16:24:100:25.
[0075] (2) Add hydrotalcite powder to the modification solution, stir at 100 rpm for 4 hours at 72°C, and dry to obtain modified hydrotalcite powder. The mass ratio of hydrotalcite powder to modification solution is 1:5.
[0076] The boron-containing flame retardant is prepared by mixing α,ω-dihydroxypolydimethylsiloxane and boric acid, stirring at 100 rpm for 6 hours at 118°C, then adding maleic anhydride, and stirring at 100 rpm for 5 hours at 90°C to obtain the boron-containing flame retardant. The mass ratio of α,ω-dihydroxypolydimethylsiloxane, boric acid, and maleic anhydride is 100:6.5:10.
[0077] Example 3 The difference between Example 3 and Example 1 is that the composition of the sheath layer is different from that of Example 1, but everything else is the same.
[0078] The sheath layer comprises the following raw materials in parts by weight: 100 parts PVC resin, 25 parts ethylene-vinyl acetate copolymer, 12 parts flame retardant, 5 parts POE-grafted glycidyl methacrylate, 5 parts methyl vinyl silicone rubber, 3 parts erucamide, 1 part calcium stearate, and 0.5 parts antioxidant 168.
[0079] The flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:0.75.
[0080] The modified hydrotalcite powder is prepared by: (1) Hexachlorotriphosphazene and octaaminopropyl cage-like polysilsesquioxane were added to acetonitrile and reacted at 85°C and 100 rpm for 7 h. Then γ-glycidoxypropyltrimethoxysilane was added and reacted at 75°C and 100 rpm for 6 h to obtain the modified solution. The mass ratio of hexachlorotriphosphazene, octaaminopropyl cage-like polysilsesquioxane, acetonitrile and γ-glycidoxypropyltrimethoxysilane was 12:18:100:20.
[0081] (2) Add hydrotalcite powder to the modification solution, stir at 100 rpm for 4 hours at 72°C, and dry to obtain modified hydrotalcite powder. The mass ratio of hydrotalcite powder to modification solution is 1:5.
[0082] The boron-containing flame retardant is prepared by mixing α,ω-dihydroxypolydimethylsiloxane and boric acid, stirring at 100 rpm for 6 hours at 118°C, then adding maleic anhydride, and stirring at 100 rpm for 5 hours at 90°C to obtain the boron-containing flame retardant. The mass ratio of α,ω-dihydroxypolydimethylsiloxane, boric acid, and maleic anhydride is 100:6.5:10.
[0083] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the composition of the sheath layer is different from that of Example 1, but everything else is the same.
[0084] The sheath layer of this comparative example comprises the following raw materials in parts by weight: 100 parts PVC resin, 22 parts ethylene-vinyl acetate copolymer, 14 parts flame retardant, 6 parts POE-grafted glycidyl methacrylate, 4 parts methyl vinyl silicone rubber, 2.5 parts erucamide, 1.5 parts calcium stearate, and 1.2 parts antioxidant 168.
[0085] The flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:0.4.
[0086] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the composition of the sheath layer is different from that of Example 1, but everything else is the same.
[0087] The sheath layer of this comparative example comprises the following raw materials in parts by weight: 100 parts PVC resin, 22 parts ethylene-vinyl acetate copolymer, 14 parts flame retardant, 6 parts POE-grafted glycidyl methacrylate, 4 parts methyl vinyl silicone rubber, 2.5 parts erucamide, 1.5 parts calcium stearate, and 1.2 parts antioxidant 168.
[0088] The flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:2.5.
[0089] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the composition of the sheath layer is different from that of Example 1, but everything else is the same.
[0090] The sheath layer of this comparative example comprises the following raw materials in parts by weight: 100 parts PVC resin, 22 parts ethylene-vinyl acetate copolymer, 14 parts flame retardant, 6 parts POE-grafted glycidyl methacrylate, 4 parts methyl vinyl silicone rubber, 2.5 parts erucamide, 1.5 parts calcium stearate, and 1.2 parts antioxidant 168.
[0091] The flame retardant is modified hydrotalcite powder.
[0092] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the composition of the sheath layer is different from that of Example 1, but everything else is the same.
[0093] The sheath layer of this comparative example comprises the following raw materials in parts by weight: 100 parts PVC resin, 22 parts ethylene-vinyl acetate copolymer, 14 parts flame retardant, 6 parts POE-grafted glycidyl methacrylate, 4 parts methyl vinyl silicone rubber, 2.5 parts erucamide, 1.5 parts calcium stearate, and 1.2 parts antioxidant 168.
[0094] The flame retardant is a boron-containing flame retardant.
[0095] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the composition of the sheath layer is different from that of Example 1, but everything else is the same.
[0096] The sheath layer of this comparative example comprises the following raw materials in parts by weight: 100 parts PVC resin, 22 parts ethylene-vinyl acetate copolymer, 14 parts flame retardant, 6 parts POE-grafted glycidyl methacrylate, 4 parts methyl vinyl silicone rubber, 2.5 parts erucamide, 1.5 parts calcium stearate, and 1.2 parts antioxidant 168.
[0097] The flame retardant comprises hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:1.
[0098] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the preparation method of the modified hydrotalcite powder is different, but everything else is the same.
[0099] The preparation method of the modified hydrotalcite powder described in this comparative example is as follows: (1) Add γ-glycidoxypropyltrimethoxysilane to water (mass ratio of the two is 1:10) and react at 75°C and 100 rpm for 6 h to obtain the modified solution; (2) Add hydrotalcite powder to the modification solution, stir at 100 rpm for 4 hours at 72°C, and dry to obtain modified hydrotalcite powder. The mass ratio of hydrotalcite powder to modification solution is 1:5.
[0100] Test case 1. The thermal stability of the sample was tested according to GB / T2951.32-2008 (mass difference, mg).
[0101] 2. UL94: Tested using a ZRS-TC type horizontal and vertical combustion test chamber, in accordance with GB / T2408-2008.
[0102] 3. Place a 20cm long cable vertically and burn it with a test torch with a flame height of 125mm and a heat power of 500W for 20 seconds, stop for 20 seconds, and repeat the burning process 5 times. Calculate the mass of the cable after it is extinguished and calculate the flame retardant protection rate. Flame retardant protection rate = (1 - damaged length / total length) 100%; the higher the flame retardant protection rate value, the better the flame retardant performance.
[0103] Table 1
[0104] As can be seen from Table 1, the cable described in this application has excellent flame retardant and fire-resistant properties.
[0105] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the technical spirit of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A flame-retardant and fire-resistant cable, characterized in that, It includes multiple conductive cores, a filling layer, a temperature-sensing optical fiber, and a sheath layer. The multiple conductive cores are arranged in a ring array inside the sheath layer. The temperature-sensing optical fiber is located between the sheath layer and the conductive cores. The filling layer fills the space between the conductive cores, the temperature-sensing optical fiber, and the sheath layer. The sheath layer comprises the following raw materials in parts by weight: 100 parts PVC resin, 20-25 parts ethylene-vinyl acetate copolymer, 12-15 parts flame retardant, 5-8 parts POE-grafted glycidyl methacrylate, 2-5 parts methyl vinyl silicone rubber, 2-3 parts lubricant, 1-3 parts stabilizer, and 0.5-2 parts antioxidant.
2. The flame-retardant and fire-resistant cable according to claim 1, characterized in that, The flame retardant comprises modified hydrotalcite powder and boron-containing flame retardant in a mass ratio of 1:(0.75~1.5).
3. The flame-retardant and fire-resistant cable according to claim 1, characterized in that, The modified hydrotalcite powder is prepared by: (1) Add hexachlorotriphosphazene and octaaminopropyl cage-like polysilsesquioxane to the solvent and react at 70~90℃ for 2~10h. Add γ-glycidyl etheroxypropyltrimethoxysilane and react at 50~80℃ for 2~10h to obtain the modified solution. (2) Add hydrotalcite powder to the modification solution, stir at 50~80℃ for 1~10h, and dry to obtain modified hydrotalcite powder.
4. The flame-retardant and fire-resistant cable according to claim 3, characterized in that, The mass ratio of hexachlorotriphosphazene, octaaminopropyl cage-like polysilsesquioxane, solvent, and γ-glycidyl etheroxypropyltrimethoxysilane is (12~16):(18~24):(50~200):(20~25); The solvent is at least one of acetonitrile, methanol, ethanol, acetone, and chloroform.
5. The flame-retardant and fire-resistant cable according to claim 3, characterized in that, The mass ratio of the hydrotalcite powder to the modified liquid is 1:(2~10).
6. The flame-retardant and fire-resistant cable according to claim 1, characterized in that, The average particle size of the hydrotalcite powder is 0.5~5μm.
7. The flame-retardant and fire-resistant cable according to claim 2, characterized in that, The boron-containing flame retardant is prepared by mixing α,ω-dihydroxypolydimethylsiloxane and boric acid, reacting at 100~140℃ for 2~10h, then adding maleic anhydride, and reacting at 80~95℃ for 2~10h to obtain the boron-containing flame retardant.
8. The flame-retardant and fire-resistant cable according to claim 7, characterized in that, The mass ratio of α,ω-dihydroxypolydimethylsiloxane, boric acid, and maleic anhydride is 100:(5~10):(8~12).
9. The flame-retardant and fire-resistant cable according to claim 1, characterized in that, The lubricant is at least one of pentaerythritol stearate, polyethylene wax, erucamide, and oleamide.
10. The flame-retardant and fire-resistant cable according to claim 1, characterized in that, The stabilizer is at least one of zinc stearate and calcium stearate.